A Study on Anxiety in Upper Primary School Students in learning Mathematics - VENKATESWARLU, KANAMARLAPUDI (THE PRIMARY TEACHER, 2016)
This study was conducted to find out anxiety in learning mathematics by upper primary school students of Prakasam district in Andhra Pradesh. The investigators adopted normative survey method for the study. A sample of 200 students from upper primary schools was selected by Systematic Random Sampling Technique. Anxiety tool was used for the study. For the analysis of data, descriptive statistics, like mean, standard deviation and ‘t’ test were employed. The findings revealed that a significant difference was found in anxiety in learning mathematics.